Connection and disconnection - Fruzsina Alexandra Németh (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
Rania Plain lies on the eastern side of Iraqi Kurdistan, at the foot of the seemingly impenetrable Zagros Mountains. During the Early Modern Period, this microregion was on the fringe of the two major powers of the Middle East, the Ottoman and Persian Empires, but it was also part of the Soran Emirate, one of the semi-autonomous vassal states that existed for hundreds of years. The Rania Plain was close to the main trade route linking Baghdad with the major Kurdish cities of Erbil and Mosul. In addition, the Lower Zab River, which flows through this valley to reach the Mesopotamian Plain, provided a natural trade and information route between the inner parts of the Zagros Mountains, the Iranian Plateau, and the fertile plains crossed by the Tigris River. Despite this, the Rania region and its cities do not appear on Ottoman Period maps, and written sources are silent about the function of the area between the 16th and 20th centuries. Field survey and excavation data from the last fifty years have provided a complex and varied picture of the valley’s topography, which, combined with the dense water network in the area, defines possible lines of population movement. One of the key questions to be addressed in examining the historical significance and complex use of the area is how to reconstruct the historical road use in the microregion using historical, archaeological, topographical, ethnographic, and GIS data and whether the area played a connecting or separating role in relation to the eastern frontier of the Ottoman Empire.